Attempts to culture the parasitic stage of Dermatobia hominis (L. Jr.) in vitro (Diptera: Cuterebridae) - Drews, Carlos (2002)
A nationwide survey in Costa Rica, using Kellert's conceptual framework (Kellert, S.R. 1996. The Value of Life. Washington D.C., Island Press), revealed at least five attitude dimensions toward animals. Overall, Costa Rican adults have a strong sentimental attitude toward animals, an expression of feelings of affection toward animals. In contrast, the materialistic attitude, which regards animals as resources and praises acts of control over them, is weak. This reflects a prevailing opposition to the act of hunting per se, rather than to its potentially detrimental effect on natural populations. There is a strong inquisitive attitude, corresponding to a widespread interest in learning about the biology of animals and their habitats. High scores on the ethical attitude indicate concern for the ethical treatment of animals and nature. The schematic attitude emphasizes the role of aesthetic appearance in the preferences for certain animals and acknowledges feelings of aversion, dislike or fear of some animals. Scores for this attitude were weakly positive. The attitude profile of Costa Ricans is probably incomplete, given the small battery of questions used in this study and differences between this and Kellert's study in the assignment of questions to particular attitudes resulting from the factor analysis. Aesthetic appeal of the animals, compassion, affection and a desire to please and stimulate the children are important motives for the acquisition of wild animals as pets. These positive feelings and a misguided empathy for animals backfire by condemning these pets to an alien environment and inadequate care. The current study also showed that adults who keep wildlife have better biological knowledge than those who never kept wildlife as pets. In addition, Costa Ricans ranked highest in the percentage of correct answers to five questions about animals, in comparison to Kellert's data for US and Japanese citizens (Kellert S.R. 1993. Journal of Social Issues 49: 53-69). Such knowledge of natural history and an animal protection profile, however, do not translate into more animal friendly practices, as seen by the keeping of wildlife as pets under conditions of concern. Rather than changing the attitudes of Costa Ricans toward animals, the challenge is to increase the awareness about the animals' needs and thereby trigger the ethical concern for their well-being. © 2002 International Society for Anthrozoology.